The behaviour of insb under the irradiation with reactor neutrons - Bolshakova, I.; Brudnyi, V.; Kolin, N.; Koptsev, P.; Kost, Ya.; Kovaleva, N.; Makido, O.; Moskovets, T.; Shoorigin, F. (Видавництво Національного університету "Львівська політехніка", 2004)
In the paper, is investigated the influence of the irradiation with full reactor neutron spectrum up to the fluence of F=31016 cm'2 upon the electrophysical properties of complex doped InSb microcrystals and thin film InSb samples with charge carrier concentration of n=(9‘1016^3‘1018) cm'3. The influence of the initial doping level on the radiation resistance is determined. The optimal charge carrier concentration for the manufacturing of the radiation resistant magnetic field microsensors is determined and is equal to n=(6^7)‘1017 cm'3 for the complex doped InSb microcrystals, and n=3-1017 cm'3 for thin film samples.